Influence of Sucrose Content on Expansion of Extruded, Starch‐Based Pellets during Microwave Vacuum Processing. Issue 6 (13th July 2014) - Kraus, Stefan; Enke, Nathanael; Schuchmann, Heike P.; Gaukel, Volker
Abstract The influence of sucrose content on microwave‐induced expansion of starch‐based, extruded pellets under vacuum was investigated. Expansion of extruded pellets with different sucrose contents (0, 10 and 20%) was investigated in a microwave vacuum‐drying system. With increasing sucrose content, volume expansion showed a nearly linear increase. Also, the number of pores increased with increasing sucrose content. A softening of the matrix might facilitate nucleation. Pore areas decrease with increasing number of pores. We therefore assume that nucleation has the strongest impact on pore area distribution. Mainly pillow‐shaped and round final products were found. The shape of the final products could be related to the glass transition temperature Tg of the intermediate products and to heating and drying characteristics of the pellets during microwave vacuum processing. Tg decreases with increasing sucrose contents. If expansion of the initially cylindrical pellets takes place within the rubbery state, round final products are formed. If a glassy outer layer is built due to evaporation cooling of the surface and high Tg of the matrix, the pellets rupture upon expansion and the pillow shape forms. Practical Applications In contrast to direct expanded extruded snacks, third‐generation snacks are generally produced by pre‐drying nonexpanded, extruded pellets, followed by a separated expansion process. By this process route, extrusion can be performed at high moisture contents, moderate temperatures and moderate shearing conditions. This is beneficial in terms of preserving thermal‐ and mechanical‐sensitive ingredients. A special feature of the process investigated in this study is that the expansion is achieved by microwave vacuum processing that allows an indirect expansion without a time‐ and energy‐consuming pre‐drying process. This study shows that total volume and inner structure of the expanded pellets is strongly influenced by the amount of sucrose added to the starch‐based matrix. With these information producers can turn structure‐related properties such as appearance, crispiness and crunchiness to target values.